The Mechanisms of Sevoflurane-Induced Neuroinflammation - Huang, Xiangfei; Ying, Jun; Yang, Danying; Fang, Pu; Wang, Xifeng; Zhou, Bin; Zhang, Lieliang; Fang, Yang; Yu, Wen; Liu, Xing; Zhen, Qingcui; Hua, Fuzhou (Frontiers in Aging Neuroscience, 2021)
Sevoflurane is one of the most commonly used inhaled anesthetics due to its low blood gas coefficient, fast onset, low airway irritation, and aromatic smell. However, recent studies have reported that sevoflurane exposure may have deleterious effects on cognitive function. Although neuroinflammation was the most widely mentioned among established sevoflurane-induced cognitive dysfunction mechanisms, its upstream mechanisms have yet to be illustrated. Thus, we reviewed the relevant literature and discussed the most mentioned mechanisms, including microglial function modulation, BBB breakdown, gut microbiota changes, and ease of cholinergic neurotransmission, to help us understand the properties of sevoflurane, providing us new perspectives for the prevention of sevoflurane-induced cognitive impairment.